(untitled) (Journal Of Educational and Psychological Researches, 2022)
This research aims to identify the cognitive distortion of kindergarten children and its relationship to their parenting reinforcement. The researcher used the descriptive approach, being the closest to reaching the study objectives, To measure the relationship between the research variables, the researcher prepared two questionnaire tools for this purpose, the first for measuring "cognitive distortion", And the second is to measure "parental reinforcement", and each tool consisted of (20) items. After ensuring the validity and reliability of the two research tools and their suitability to measure the studied phenomenon, the researcher chose a random sample of the parents of the Kindergarten children, from four governmental and private Kindergarten belonging to AL-Risaffa (1) District of Baghdad governorate, their number reached (200) male guardians of both sexes. After the completion of data collection and statistical analysis by using the statistical application (SPSS), The researcher concluded that there is an inverse correlation between cognitive distortion and parental reinforcement in kindergarten children, The lower the parental reinforcement, the greater the percentage of cognitive distortions they have, and vice versa. Therefore, the researcher recommended that parents of kindergarten children should increase parental strengthening towards their children, which contributes to enhancing their confidence and reducing their cognitive distortion.